Assessing nontarget effects and host feeding of the exotic parasitoid Apanteles taragamae, a potential biological control agent of the cowpea pod borer Maruca vitrata - Dannou, E.A.; Tamò, Manuele; Huis, A. van; Dicke, M. (Springer, 2012)
Apanteles taragamae Viereck is a larval parasitoid introduced in Benin for classical biological control of the cowpea pod borer Maruca vitrata Fabricius. In the laboratory, we evaluated the effects of A. taragamae on non-target herbivore species, and on another parasitoid of M. vitrata, i.e. the egg-larval parasitoid Phanerotoma leucobasis Kriechbaumer. Furthermore, we addressed the host feeding behaviour of A. taragamae. The host specificity of A. taragamae was assessed by offering six other lepidopteran species to the wasp. The competitive ability of A. taragamae was studied by providing the wasp with one- and two-days-old M. vitrata larvae that had hatched from eggs previously parasitized by P. leucobasis. Controls consisted of eggs and larvae offered only to P. leucobasis and A. taragamae, respectively. None of the other six lepidopteran species was successfully parasitized by A. taragamae. The larval parasitoid A. taragamae outcompeted the egg-larval parasitoid P. leucobasis when offered two-days-old host larvae. Competition between the two parasitoid species did not significantly affect one-day-old host larvae that were less suitable to A. taragamae. Host feeding by A. taragamae did not affect survival of one-day-old or two-days-old M. vitrata larvae. However, the percentage parasitism of two-days-old larvae was significantly reduced when exposed to female A. taragamae wasps that had been starved during 48 h. The data are discussed with regard to host specificity, host feeding patterns and to factors underlying the outcome of intrinsic competition between parasitoid species.